Flutter Control of a Lifting Surface via Visco-Hysteretic Vibration Absorbers - Lacarbonara, Walter; Cetraro, Marek (International journal of aeronautical and space sciences, 2011)
In this paper, a visco-hysteretic vibration absorber (VA) is proposed to increase the flutter speed of an airfoil and enhance damping in the pre- and post-flutter regimes. The passive system consists of a parallel arrangement of a dashpot and a rateindependent hysteretic element, represented by the Bouc-Wen differential model. The equations of motion are obtained and various tools of linear and nonlinear dynamics are employed to study the effects of the visco-hysteretic VA in the pre- and post-flutter ranges. KCI Citation Count: 0